The Need and Importance of Modern Lectures in Higher Education - Rakhimov Oktyabr Dustkabilovich; Azizova Iroda Furkatovna (EDUMALSYS Journal of Research in Education Management, 2026)
The rapid expansion of modern information and communication technologies and the development of distance learning have renewed debates on how educational models and organizational forms should be aligned in higher education. This article examines the relationship between the educational model and the organizational form of teaching by focusing on the contemporary lecture as a central element of the higher education instructional process. Through a historical and conceptual analysis, the article traces the emergence and evolution of lectures in higher education, outlines the current forms and pedagogical necessity of modern lectures, and distinguishes their main characteristics and functions. Particular attention is given to the distinction between passive and active lectures, the respective roles of teachers and students within these formats, and the ways in which different lecture designs contribute to engagement and learning outcomes. The analysis highlights that, despite the diversification of instructional formats enabled by digital technologies, the modern lecture retains a pivotal place in the formation of professional competence among future specialists when it is aligned with innovative, student-centered, and technology-enhanced educational models. The study concludes that a pedagogically reoriented lecture—integrated with active learning strategies and informed by contemporary information and communication technologies—can effectively support the development of professional competence and should remain a core organizational form within higher education.